Understanding the impact of one-dimensional pore containing 10MR and 12MR and aluminium content on MTH reaction pathways: direct synthesis of heteroatom containing UZM-55. Issue 3 (2nd January 2020) - Galey, Melissa M.; Miller, Mark A.; Lanuza, Mary; Prabhakar, Sesh; Nicholas, Christopher P.
Abstract : We directly synthesized one-dimensional zeolite UZM-55 as an aluminosilicate and catalyzed MTH to understand pore structure influence on catalytic properties. Abstract : Zeolites are utilized in many catalytic applications on large scale, and we report here the direct synthesis of alumino- and borosilicate versions of UZM-55, a recent unidimensional (1D) zeolite with a kinked channel containing both 10MR and 12MR. Up to approximately one heteroatom per unit cell has been incorporated, and the aluminosilicate forms tested for the MTH reaction. UZM-55 shows very high selectivity to propene at ∼51%, <5% selectivity to ethene, and high selectivity to C3 + C4 products of ∼76–79%. Unlike other 1D zeolites containing 12MR, UZM-55 clearly favors the olefin cycle mechanism.